PENANGGULANGAN TINDAK PIDANA MAIN SENDIRI OLEH MASYARAKAT (Studi Penelitian pada Kepolisian Sektor Babussalam Kabupaten Aceh Tenggara) - Riska Sintania SKD; Husni H; Teuku Yudi Afrizal (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2022)
Judgment itself is an arbitrary act against people who are considered guilty. This is contrary to Article 170 of the Criminal Code paragraph (1) which reads "Anyone who in public together commits violence against people or goods, is sentenced to a maximum imprisonment of five years and six months". However, vigilante action still occurs as is the case in Kutarih Village, Babussalam District, Southeast Aceh Regency.The purpose of this study is to find out and explain the forms of countermeasures carried out by the Babussalam Sector Police against vigilante crimes by the community and the obstacles faced by the Babussalam Sector Police in tackling vigilante crimes by the community.This type of research is qualitative with an empirical juridical approach, is descriptive in the form of prescriptive research. Sources of data used are primary data in the form of interviews with respondents and informants.Based on the research results it is known that; The form of countermeasures carried out by the Babussalam Sector Police against vigilante crimes by the community is through preventive and repressive measures. Preventive actions include outreach to the community, fostering public trust in law enforcement officials, establishing partnerships with the community, carrying out formal and informal education, and carrying out routine patrols. While the repressive actions are; investigate cases to completion, collect evidence, and impose sanctions on perpetrators of vigilante crimes. The obstacles faced by the Babussalam Sector Police in tackling the crime of vigilantism by the community are that it is difficult to predict or is spontaneous; community conditions are heating up so that police officers seem to be working alone to secure victims, lack of good cooperation between the police and the local community to jointly tackle any vigilante action, no one in the community is willing to be a witness to vigilante acts; and many people who take part in vigilantism do not know who is involved.It is recommended to the police to further improve preventive actions so that these actions can be reduced or lost by providing legal awareness to the community, especially in the jurisdiction of the Babussalam Police, increasing coordination and cooperation with community leaders, religious leaders, government officials, non-governmental organizations. community and others. It is hoped that the police will be able to increase cooperation with the community in tackling vigilante acts and be able to investigate thoroughly by collecting evidence at the crime scene so that the culprit can be found.